Effects of ensiling treatments on lactic acid production and supplementary methane formation of maize and amaranth – An advanced green biorefining approach. (February 2015) - Haag, Nicola Leonard; Nägele, Hans-Joachim; Fritz, Thomas; Oechsner, Hans
Highlights: Maize and amaranth were treated with different ensiling techniques. Biomethanation was observed from silage and separated residue in digestion tests. Lactic acid was increased about 91.9% in maize silage. Specific methane yield of silage compared to solid residue was similar for maize. Lactic acid and biogas were produced to a remarkable extent. Abstract: A green biorefinery enables the material and energetic use of biomass via lactic acid and methane production. Different ensiling techniques were applied to maize and amaranth with the aim to increase the amount of lactic acid in the silage. In addition the methane formation potential of the ensiled samples and the remaining solid residues after separating the organic juice were assessed. Treating maize with homofermentative lactic acid bacteria in combination with carbonated lime increased the amount of lactic acid about 91.9%. For amaranth no additional lactic acid production was obtained by treating the raw material. Specific methane yields for the solid residues of amaranth were significantly lower in comparison to the corresponding silages. The most promising treatment resulted in a production of 127.9 ± 4.1 g kg −1 DM lactic acid and a specific methane yield for the solid residue of 349.5 ± 6.6 lN kg −1 ODM.